Identification of non-equilibrium growth for Bitcoin Exchange rate: Mathematical derivation method in Islamic Financial Engineering - Bakar, Nashirah Abu; Rosbi, Sofian (International Journal of Scientific Research and Management (IJSRM), 2017)
Crptocurrency is a type of digital currency that using decentralized method for validating transaction. In the same time, the user of the Bitcoin is protected using hash algorithm. The value of Bitcoin is increased sharply in 2017 that creates much attention from investors. The objective of this study is to develop the mathematical model evaluate growth of Bitcoin exchange rate. The data selected in this study are starting from 1st January 2017 until 10th December 2017. This study validates the normality distribution of data using graphical and numerical method. Graphical method indicates the first difference of data distribution is a non-normal distribution. Then, Shapiro-Wilk statistical test confirmed that first difference of data distribution deviate from normal distribution. The non-normal distribution occurs because of the presence of outliers. Next, this study validates the mathematical modeling fordata trend using quadratic formula. Result indicates that the growth of Bitcoin exchange rate in moving towards non-equilibrium point. This concludes that the growth of the Bitcoin exchange rate is in unstable region.  The contribution of this study is to help investors to understand the nature of Bitcoin exchange rate. This study performed analysis that helps investors to develop more efficient investment portfolio in gaining better profit and reducing loss